Tyrosine Kinase Inhibitors Play an Antiviral Action in Patients Affected by Chronic Myeloid Leukemia: A Possible Model Supporting Their Use in the Fight Against SARS-CoV-2 - Galimberti, Sara; Petrini, Mario; Baratè, Claudia; Ricci, Federica; Balducci, Serena; Grassi, Susanna; Guerrini, Francesca; Ciabatti, Elena; Mechelli, Sandra; Di Paolo, Antonello; Baldini, Chiara; Baglietto, Laura; et al. (Frontiers in Oncology, 2020)
SARS-CoV-2 is the viral agent responsible for the pandemic that in the first months of 2020 caused about 400,000 deaths. Among compounds proposed to fight the SARS-CoV-2-related disease (COVID-19), tyrosine kinase inhibitors (TKIs), already effective in Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) and chronic myeloid leukemia (CML), have been proposed on the basis of their antiviral action already demonstrated against SARS-CoV-1. Very few cases of COVID-19 have been reported in Ph+ ALL and in CML Italian cohorts; authors suggested that this low rate of infections might depend from the use of TKIs, but the biological causes of this phenomenon remain unknown. In this study, the CML model was used to test if TKIs would sustain or not the viral replication and if the patient immunity could be damaged by them. Firstly, infection and replication rate of Torquetenovirus (TTV), that load is inversely proportional to the host immunological control, have been measured in CML patients receiving Nilotinib. A very low percentage of subjects resulted infected at baseline and TTV did not replicate or at least showed a low replication rate during the follow-up, with mean load comparable to the measured one in healthy subjects. Then, after gene expression profiling experiments, we found that several “anti-viral” genes, such as CD28 and IFN gamma, were up-regulated, whilst genes with “pro-viral” action, such as ARG1, CEACAM1 and FUT4 resulted less expressed during treatment with Imatinib, thus demonstrating that TKIs are not detrimental from the immunological point of view. To sum up, our data could offer some biological explanations to the low COVID-19 occurrence in Ph+ ALL and CML patients and sustain the use of TKIs in COVID-19, as already proposed by several international ongoing studies.